First-principles investigation of Ag-, Co-, Cr-, Cu-, Fe-, Mn-, Ni-, Pd- and Rh-hexaaminobenzene 2D metal-organic frameworks - Mortazavi, Bohayra; Shahrokhi, Masoud; Makaremi, Meysam; Cuniberti, Gianaurelio (Giovanni); Rabczuk, Timon (Materials Today Energy, 2018)
Hexaaminobenzene (HAB)-derived two-dimensional metal−organic frameworks (MOFs) (Nature Energy 3(2018), 30–36) have most recently gained remarkable attentions as a novel class of two-dimensional (2D) materials, with outstanding performances for advanced energy storage systems. In the latest experimental advances, Ni-, Co- and Cu-HAB MOFs were synthesized in 2D forms, with high electrical conductivities and capacitances as well. Motivated by these experimental advances, we employed first-principles simulations to explore the mechanical, thermal stability and electronic properties of single-layer Ag-, Co-, Cr-, Cu-, Fe-, Mn-, Ni-, Pd- and Rh-HAB MOFs. Theoretical results reveal that Co-, Cr-, Fe-, Mn-, Ni-, Pd- and Rh-HAB nanosheets exhibit linear elasticity with considerable tensile strengths. Ab-initio molecular dynamics results confirm the high thermal stability of all studied nanomembranes. Co- and Fe-HAB monolayers show metallic behavior with low spin-polarization at the Fermi level. Single-layer Ag-, Cu-, Cr-, and Mn-HAB however yield perfect half-metallic behaviors, thus can be promising candidates for the spintronics. In contrast, Ni-, Pd- and Rh-HAB monolayers exhibit nonmagnetic metallic behavior. The insights provided by this investigation confirm the stability and highlight the outstanding physics of transition metal-HAB nanosheets, which are not only highly attractive for the energy storage systems, but may also serve for other advanced applications, like spintronics.
CRIS-Team Scopus Importer:2022-04-14
Keywords: 2D materials; Energy storage; First-principles; MOFs